Experimental research on statics bond performance of reinforcement-concrete interface after the combined action of corrosion and fatigue - Wang, Bowen; Liu, Yang; Luo, Dong; Yuan, Heping (Frontiers in Materials, 2022)
Corrosion of reinforced bars and the fatigue effect in concrete structures significantly impact the bond performance of reinforced bars. Current research has focused on the influence of fatigue or corrosion on the bond performance of reinforced bars. However, there is a combined action of fatigue and corrosion in the process of structural service. The degradation law of the bond performance, failure characteristics, and changing trend of bond stress along the anchorage length of RC specimens were analyzed under the combined action of fatigue and corrosion in this test. Only pulling out of the reinforced bar was occurred in specimens under corroded action, whereas breaking or pulling out of the reinforced bar could be occurred under the combined action of corrosion and fatigue. The longitudinal distribution curve of bond stress of the specimens only has a single peak under the action of fatigue or corrosion. However, there are double peaks in the bond stress curve under the combined action of fatigue and corrosion. The ultimate values of the bond stress and slip in the specimens decrease significantly under the combined action of corrosion and fatigue.